A probabilistic analysis of the dynamic response of monopile foundations: Soil variability and its consequences. (July 2015) - Damgaard, M.; Andersen, L.V.; Ibsen, L.B.; Toft, H.S.; Sørensen, J.D.
Abstract: The reliability of offshore wind turbines is highly influenced by the uncertainties related to the subsoil conditions. Traditionally, the evaluation of the dynamic structural behaviour is based on a computational model with deterministic soil properties. Using this approach, however, provides limited insight into the variation of the estimate of the inherent modal properties and loads. In this paper, a comprehensive study is performed on the dynamic behaviour of an offshore wind turbine installed on a monopile foundation. Based on consistent lumped-parameter models calibrated to semi-analytical impedance functions of a monopile embedded in a stochastic linear viscoelastic soil layer, fully coupled aero-hydro-elastic simulations are conducted in the nonlinear multi-body code Hawc2 . The probabilistic analysis accounts for the uncertainty of soil properties ( e.g. damping and stiffness) and relies on a Monte Carlo method facilitating the derivation of the probability densities of the modal properties and the fatigue loading. The main conclusion of the presented work is that the dynamic structural behaviour of the wind turbine and its support structure is strongly affected by the stochastic soil properties. Lognormal and Gumbel distributed modal damping and accumulated side–side fatigue damage equivalent moments with a coefficient of variation of 30% and 8%, respectively, are observed. Abstract : Highlights: Soil variability and its influence on the dynamic behaviour of an offshore wind turbine is investigated A negative skew distribution (beta distribution) of the first natural frequency is obtained. The modal damping related to lowest eigenmode strongly depends on the soil properties. The observed variations of the modal properties of the wind turbine cause distinctly varying fatigue loads in the side–side direction.